2015
DOI: 10.1590/s1679-45082015ao3243
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low-level laser therapy on vertical jump in sedentary individuals

Abstract: Objective To investigate the effects of low intensity laser (660nm), on the surae triceps muscle fatigue and power, during vertical jump in sedentary individuals, in addition to delayed onset muscle soreness.Methods We included 22 sedentary volunteers in the study, who were divided into three groups: G1 (n=8) without performing low intensity laser (control); G2 (n=7) subjected to 6 days of low intensity laser applications; and G3 (n=7) subjected to 10 days of low intensity laser applications. All subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…Similar to the wavelength used by Almeida et al 32 , comparing the 830 nm to 660 nm, but found that both wavelengths promoted increased peak power and delayed fatigue of the biceps muscle. As noted above, recent studies have addressed the efficacy of LLLT in muscle performance, however, other studies did not show superior effects to the control with laser therapy, mainly due to enormous parameters variation of therapy 33,34 . In the present study, it was sought to use a commercial equipment with routinely used parameters in order to analyze if the LLLT application provide any change in proprioception, improving balance, and other variables, data from baropodometry referring to pressure from the feet were analyzed, distance from the center and even to the plantar surface, since the skin sensory stimulation plant contributes to the march and postural control, providing information on the compensatory reactions 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the wavelength used by Almeida et al 32 , comparing the 830 nm to 660 nm, but found that both wavelengths promoted increased peak power and delayed fatigue of the biceps muscle. As noted above, recent studies have addressed the efficacy of LLLT in muscle performance, however, other studies did not show superior effects to the control with laser therapy, mainly due to enormous parameters variation of therapy 33,34 . In the present study, it was sought to use a commercial equipment with routinely used parameters in order to analyze if the LLLT application provide any change in proprioception, improving balance, and other variables, data from baropodometry referring to pressure from the feet were analyzed, distance from the center and even to the plantar surface, since the skin sensory stimulation plant contributes to the march and postural control, providing information on the compensatory reactions 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Kakihata et al, 2015 (28) To evaluate the effects on the fatigue and the muscle power in 22 sedentary women with a mean age of 21.21±2.8 years.…”
Section: Authors and Year Objectives/sample Wavelength Dose/number Ofmentioning
confidence: 99%
“…The sample of this study consisted, then, of 27 articles published in the years 2008 11 ,2009 12-14 , 2010 2,15,16 , 2011 17 , 2012 18-20 , 2013 10,21,22 , 2014 23-26 , 2015 27,28 , 2016 [29][30][31][32][33][34] and 2017 35 . Of these, only three (11.1%) were published in Portuguese 10,16,28 . The other ones are in English, but all of them (100.0%) were produced by Brazilian authors.…”
Section: Infrared 3 J Per Point -8 Points On the Abductor Muscle -24 mentioning
confidence: 99%
See 2 more Smart Citations